Ecological dynamics of stink bugs that attack soybean and corn ﬁelds in the Neotropical region - Rodrigues, Hígor de Souza (Universidade Federal de Viçosa, 2021)
Soybean and corn are the two most representative crops of Brazilian agribusiness. However, during the crop development cycle factors such as pest insect attack, especially the Neotropi- cal brown stink bug, Euschistus heros, and the green belly stink bug, Diceraeus melacanthus, can reduce productivity and require care. Thus, tools to compose an integrated pest management (IPM) program become necessary to minimize the losses caused by these arthropods. Based on that, this thesis was constructed with the objectives of evaluating the competitive ability of E. heros and D. melacanthus, verifying the toxicity of different insecticide groups and the detoxiﬁ- cation capacity of these insects under different temperatures and generating products (ie, maps of suitability) that indicate safer locations with greater risk of cultivation in the face of attack by these two pentatomids based on the current climate, thus generating preventive control tools for a bed bug MIP program. Euschistus heros was more competitive than D. melacanthus since the presence of its heterospeciﬁc did not impact the number of live insects. However, when the heterospeciﬁc was not present, D. melacanthus caused lower pod production and increa- sed its growth rate. Diceraeus melacanthus was also the most tolerant species to imidacloprid compared to E. heros [RR 50 =15.32 (4.9-48.1)], and was the species that had the most enzymatic detoxiﬁcation when subjected to temperature changes (ie, 20 °C) with mortality at the LC 50 re- duced by 47.96%. Another result produced in this work was climate-based prediction models (i.e., ecological niche models). Model indicators were satisfactory for both species: for E. heros, the AUC (Area Under Curve) was 0.99 ± 0.01 and the TSS (True Skill Statistic) was 0.95 ± 0.03; for D. melacanthus, the AUC was 0.94 ± 0.04 and the TSS was 0.95 ± 0.03. Our forecast indicates greater potential damage from E. heros in the center-west of Brazil and in the west of Bahia, while D. melacanthus concentrates greater potential damage in the center-south of the country. This thesis then shows that despite the greater impact of D. melacanthus on pod reduction, E. heros was more competitive than D. melacanthus in the presence of both species, which justiﬁes its abundance; however, D. melacanthus may prove to be a major problem in the absence of E. heros. Furthermore, this study also showed the impact of insecticides on both species and in- dicates that some molecules may not be more effective at commonly used doses and that their detoxiﬁcation may be increased at low temperatures. Finally, we indicate, through ecological niche models, safe areas and areas with greater risks of soy and corn production against the attack of these insects. All studies carried out here suggest tools to be incorporated into a bed bug MIP program, helping with decision-making and contributing to the management of these pests in production ﬁelds. Keywords: Euschistus heros. Diceraeus (Dichelops) melacanthus. Enzymatic detoxiﬁcation. Inters- peciﬁc competition. Ecological niche modeling.

A soja e o milho são as duas das mais representativas culturas do agronegócio brasileiro. No entanto, durante o ciclo de desenvolvimento da cultura fatores como o ataque de insetos-praga, com destaque para o percevejo-marrom da soja, Euschistus heros, e o percevejo barriga-verde, Diceraeus melacanthus, podem reduzir a produtividade e requerem cuidados. Com isso, ferra- mentas para compor um programa de manejo integrado de pragas (MIP) se tornam necessá- rias para minimizar as perdas provocadas por esses artrópodes. Neste sentido, essa tese foi construída com os objetivos de avaliar a habilidade competitiva de E. heros e D. melacanthus, averiguar a toxicidade de diferentes grupos inseticidas e a capacidade de detoxiﬁcação desses insetos sob diferentes temperaturas e gerar produtos (i.e., mapas de adequabilidade) que indi- quem locais com mais segurança e com maior risco de cultivo frente ao ataque desses dois pen- tatomídeos com base no clima atual, gerando assim ferramentas preventivas de controle para um programa de MIP de percevejos. Euschistus heros foi mais competitivo que D. melacanthus visto que a presença de seu heteroespecíﬁco não impactou o número de insetos vivos. Todavia, quando não houve presença do heteroespecíﬁco, D. melacanthus provocou menor produção de vagens e aumentou sua taxa de crescimento. Diceraeus melacanthus também se mostrou a espé- cie mais tolerante a imidaclopride comparada a E. heros [RR 50 =15.32 (4.9-48.1)], e foi a espécie que mais teve detoxiﬁcação enzimática quando submetido a mudanças de temperatura (i.e., 20 °C) com a mortalidade na CL 50 reduzida em 47.96%. Outro resultado produzido neste trabalho foram modelos de previsão (i.e., modelos de nicho ecológico) baseados em clima. Os indicado- res dos modelos foram satisfatórios para ambas as espécies: para E. heros, o AUC (Area Under Curve) foi 0.99 ± 0.01 e o TSS (True Skill Statistic) foi 0.95 ± 0.03; para D. melacanthus, o AUC foi 0.94 ± 0.04 e o TSS foi 0.95 ± 0.03. Nossa previsão indica maiores danos potenciais de E. heros no centro-oeste do Brasil e no Oeste da Bahia, já D. melacanthus concentra maiores danos potenciais no centro-sul do país. Esta tese então mostra que apesar do maior impacto de D. melacanthus na redução de vagens, E. heros foi mais competitivo que D. melacanthus na presença das duas espécies, o que justiﬁca sua abundância; porém, D. melacanthus pode vir a ser um grande problema na ausência de E. heros. Além disso, este estudo tambêm mostrou o impacto de inseticidas nas duas espécies e indica que algumas moléculas podem não ser mais eﬁcazes em doses comumente usadas e ainda que sua detoxiﬁcação pode ser aumentada em baixas temperaturas. Por ﬁm, indicamos através de modelos de nicho ecológico, áreas seguras e àreas com maiores riscos de produção de soja e milho frente ao ataque desses insetos. Todos os es- tudos realizados aqui sugerem ferramentas a serem incorporadas em um programa de MIP de percevejos, ajudando nas tomadas de decisão e contribuindo para o manejo dessas pragas nos campos de produção. Palavras-chave: Euschistus heros. Diceraeus (Dichelops) melacanthus. Detoxiﬁcação enzimática. Competição interespecíﬁca. Modelagem de nicho ecológico.
Keywords: Euschistus heros; Diceraeus melacanthus; Competição (Biologia); Nicho (Ecologia); Modelagem; Entomologia Agricola